Yellow earth - Sayles, John 1950- (Haymarket Books, 2020)
When rich layers of shale oil are discovered beneath the town of Yellow Earth, all hell breaks loose. Locals, oil workers, service workers, politicians, law enforcement, and get-rich-quick opportunists--along with an earnest wildlife biologist--commingle and collide as the population of the town triples overnight. Harleigh Killdeer, chairman of the tribal business council of neighboring Three Nations reservation, wants to increase economic opportunity but faces opposition for extolling "sovereignty by the barrel." From casino dealers and geologists to Native activists and high school kids, everyone in the region is swept up in the unsparing wave of an oil boom
Keywords: Shale oils / Refining / Fiction; Oil-shale industry / Fiction; Indian reservations / North Dakota / Fiction; Indians of North America / Fiction; North Dakota / Fiction; FICTION / Action & Adventure; FICTION / Native American & Aboriginal; FICTION / Political; FICTION / Sagas; Indian reservations; Indians of North America; Oil-shale industry; Shale oils / Refining; North Dakota; Fiction; Novels